International Capital Flows at the Security Level : Evidence from the ECB's Asset Purchase Programme - Bergant, Katharina (IMF Working Papers; Working Paper ;, 2020)
We analyse euro area investors' portfolio rebalancing during the ECB's Asset Purchase Programme at the security level. Our empirical analysis shows that euro area investors (in particular investment funds and households) actively rebalanced away from securities targeted under the Public Sector Purchase Programme and other euro-denominated debt securities, towards foreign debt instruments, including `closest substitutes', id est certain sovereign debt securities issued by non-euro area advanced countries. This rebalancing was particularly strong during the first six quarters of the programme. Our analysis also reveals marked differences across sectors as well as country groups within the euro area, suggesting that quantitative easing has induced heterogeneous portfolio shifts.